The impact of the uses of digital devices on the right to privacy: risks and legal protection - Kheleifia, Houda (Journal of Human Sciences, 2022)
Science gave human kind a lot of progress in all fields, and the fields of technology and media had the largest share in what the human mind has attained of knowledge and digital devices are among the most prominent manifestations of progress and advancement, after the revolution of computers, telephones, telegrams and faxes, the revolution of mobile phones smart boards, high-definition surveillance cameras, remote tracking devices, and others.And through this study, we will try to get acquainted with the reality of the uses digital devices and their impact on the lives of people and their privacy and their risks to private life and then identify the legislative and legal challenges that the Algerian legislator has taken to protect the right to privacy from the illegal use of digital devices in front of the rapid trend and excessive towards it from the Algerian society in all its categories.